Hubungan Perilaku Ibu Dalam Pemberian Makan Dengan Status Gizi Balita Di Wilayah Kerja Puskesmas Putri Ayu Kota Jambi - Fariska Rian Elfandes; Fadliyana Ekawati; Yulia Indah Permata Sari (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Nutritional status is a state of balance between the intake of nutrients consumed and the nutrients needed by the body which can be measured and assessed by child anthropometry. One of the dominant factors and can affect the nutritional status of toddlers is the attitude and behavior of mothers who lack awareness of the importance of toddler nutrition. The relationship between maternal behavior in feeding with the nutritional status of toddlers in the working area of the Putri Ayu Health Center, Jambi City is known. This study included quantitative research using a cross sectional design. The number of samples was 105 samples. Using the Spearman Rho statistical test. The results showed good maternal behavior obtained (88.6%), poor maternal behavior obtained (11.4%). Nutritional status of toddlers with good nutrition was obtained (79.0%), overnutrition (5.7%), undernutrition (8.5%) and poor nutrition was obtained (6.7%). The results of the Spearman Rho statistical test obtained a correlation coefficient of 0.587. The results showed that there was a relationship between maternal behavior in feeding with the nutritional status of toddlers in the Working Area of the Putri Ayu Health Center in Jambi City because the majority of respondents had good education and economic levels. It is expected that the community will increase their literacy from various sources related to toddler nutrition, especially for mothers who have toddlers to increase knowledge. The more public knowledge of the nutritional status of toddlers increases, the better the behavior of mothers in toddlers will be and the nutritional status of toddlers will increase.